1977
DOI: 10.1111/j.1502-3885.1977.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Subaquatic flow tills: a new interpretation for the genesis of some laminated till deposits

Abstract: Detailed field mapping, till fabric, granulometric, and thin section investigations indicate that a 500 m long unit of laminated tills and interstratified glaciofluvial and glaciolacustrine sediments, belonging to the Catfish Creek Formation and exposed along the north shore of Lake Erie, Ontario, were deposited contemporaneously into a proglacial lake by coherent subaqueous mass flows of till (subaquatic flow tills) accompanied by glaciofluvial and glaciolacustrine contribution from supra‐ and/or subglacial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 22 publications
3
49
0
1
Order By: Relevance
“…proximal to or beneath an ice mass by a combination of rain-out, current reworking and flow remobilization (e.g. Evenson et al, 1977;Gibbard, 1980;Eyles, 1987;Eyles et al, 1989;Bennett et al, 2006;Lee and Phillips, 2008;Ravier et al, 2014a). This agrees with previous work by Piotrowski (1994a), although we extend the interpretation to include 'melt-out' tills of his upper complex (Piotrowski, 1992(Piotrowski, , 1996.…”
Section: Grain Size Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…proximal to or beneath an ice mass by a combination of rain-out, current reworking and flow remobilization (e.g. Evenson et al, 1977;Gibbard, 1980;Eyles, 1987;Eyles et al, 1989;Bennett et al, 2006;Lee and Phillips, 2008;Ravier et al, 2014a). This agrees with previous work by Piotrowski (1994a), although we extend the interpretation to include 'melt-out' tills of his upper complex (Piotrowski, 1992(Piotrowski, , 1996.…”
Section: Grain Size Analysissupporting
confidence: 86%
“…LFA N2, Fig. 6) represent discrete sediment-density flows (Evenson, 1977;Eyles et al, 1987) and pulses of debris raining out from an iceroof (Gibbard, 1980;Bennett et al, 2006). Subaqueous sedimentation of diamicton through a water column by low-energy rain-out is best illustrated at LFA N2 where underlying ripple structures have been preserved and are conformably overlain by diamicton (Fig.…”
Section: Grain Size Analysismentioning
confidence: 97%
“…Rotation and shearing of clasts may indicate that transient deformation and lodgement processes were operating beneath the ice that deposited SU3 (Evans et al 2006;Piotrowski et al 2006). Thick, stacked sequences of diamicton and stratified sediment attributed to SU3 in the southern part of the county may record ice-marginal sedimentation as debris flows (flow tills) during the retreat phase of SU3 (Evenson et al 1977). Depletion of carbonate and colour staining in the upper part of SU3 indicate prolonged subaerial exposure and incipient soil development following glacier retreat (Karrow et al 2001).…”
Section: Su3: Lower Fine-grained Tillmentioning
confidence: 99%
“…Chaney et al (1997) interpreted the 'rainout' diamictite as high energy glacial melt water deposit accumulated in close proximity to ice sheets in the Australian coal basins. Evenson et al (1977) suggested that the glacial melt water currents ripped up the earlier formed beds and transported down slope as coherent blocks along with ice rafted debris to deposit as intraformational clasts in diamictite similar to those shown in Fig. 8e.…”
Section: Coal Forming Environmentsmentioning
confidence: 77%